Geographic and temporal variations in strandings of beaked whales (Ziphiidae) on the coasts of the UK and the Republic of Ireland from 1800-2002 - MacLeod , Colin D.; Pierce , Graham J.; Santos , M. Begona (J. Cetacean Res. Manage., 2023)
This study analyses published records of beaked whale strandings from the coasts of the UK and the Republic of Ireland between 1800 and 2002. Strandings of northern bottlenose whales (Hyperoodon ampullatus) were lowest in April and highest in September. The number of strandings between months differed significantly from an even spread over all months of the year, with more strandings between July and October. Most strandings in late summer and autumn occurred on North Sea coasts and their stomach contents included the squid Gonatus fabricii, which is found only in more northern waters. This suggests that these whales may be migrating southward at this time of year. Most strandings of Sowerby’s beaked whales (Mesoplodon bidens) also occurred in late summer and autumn, although this was not significant. Strandings of Cuvier’s beaked whales (Ziphius cavirostris) occurred almost exclusively on the Atlantic coasts of the UK and in Ireland. There were significantly more Cuvier’s beaked whale strandings than expected in January and February and in June and July. A Cuvier’s beaked whale which stranded in northern Scotland in February contained similar prey to two whales stranded in north-western Spain at the same time of year, suggesting this animal could have been feeding in more southern waters prior to stranding. Seasonal patterns of strandings of northern bottlenose and Cuvier’s beaked whales were significantly different with more of the former stranding in August to October and more of the latter from November to July. This is consistent with a hypothesis of temporal segregation between the two species to reduce potential competition for prey.